PENERAPAN ALAT BANTU PEMBELAJARAN UNTUK MENINGKATKAN HASIL BELAJAR SHOOTING BOLA BASKET - Tomi Hendra; Agus Mukholid (PJKR FKOR UNS, 2017)
This research aims at improving the learning outcome of the basketball shooting basis technique on the VIII-A grade students of SMP Negeri 14 Surakarta in the Academic Year of 2016/2017.This research is conducted in two cycles in which each cycle consists of two meetings. The subjects of this research are 30 VIII-A grade students of SMP Negeri 14 Surakarta with 16 female students and 14 male students. The data collection technique uses observation, test, and documentation. The data validity uses data triangulation technique. The data are analyzed using qualitative and quantitative.The research finding in the pre-cycle was that there were only 12 students who passed (40%) and the other 18 students had not passed (60%). In the cycle I, there were 19 students passed (63.3%) and 11 students still had not passed (36.67%) with the average score of affective (60%), psychomotor (76.67%), and cognitive (66.67%). In the cycle II it is obtained that there were 25 passed-students (83.33%) and 5 students still had not passed (16.67%). With the average score of affective (80%), psychomotor (83.33%), and cognitive (86.67%). Based on the analysis result on the cycle I & II, it shows an increase in learning outcome of basketball shooting.